Lectin-mediated biofilm maturation, quorum sensing and Pseudomonas aeruginosa infections in cystic fibrosis - Crusz, S.A. (2009)
Chronic infections with Pseudomonas aeruginosa are primarily responsible for the decline in lung function and ultimate mortality in cystic fibrosis patients. The overall aim of this project was to elucidate some of the molecular mechanisms governing the pathogenesis of P. aeruginosa in the cystic fibrosis lung. This was with particular reference to (a) quorum sensing, a cell-to-cell communication system controlling the production of virulence determinants in a population density dependent manner using diffusible signal molecules and (b) the pseudomonas lectins, LecA and LecB, which are known to contribute to biofilm formation. Serial sputum samples were collected from adult and paediatric patients with cystic fibrosis and a cohort of clinical P. aeruginosa isolates was assembled. Using bioreporters, these isolates were shown to synthesise a range of quorum sensing signal molecules. Furthermore, the direct detection of these P. aeruginosa products from infected sputum samples in conjunction with patient clinical data implied an association between sputum quorum sensing signal molecule level and cystic fibrosis disease status, response to intravenous antibiotics and the presence of non-culturable P. aeruginosa.